Clinical Correlates of Human Immunodeficiency Virus–1 (HIV-1) DNA and Inducible HIV-1 RNA Reservoirs in Peripheral Blood in Children With Perinatally Acquired HIV-1 Infection With Sustained Virologic Suppression for at Least 5 Years. (28th March 2019) - Bitnun, Ari; Ransy, Doris G; Brophy, Jason; Kakkar, Fatima; Hawkes, Michael; Samson, Lindy; Annabi, Bayader; Pagliuzza, Amélie; Morand, Jacob-Adams; Sauve, Laura; Chomont, Nicolas; Lavoie, Stephanie; et al.
Abstract: Background: The Early Pediatric Initiation Canada Child Cure Cohort (EPIC 4 ) study is a prospective, multicenter, Canadian cohort study investigating human immunodeficiency virus–1 (HIV-1) reservoirs, chronic inflammation, and immune responses in children with perinatally acquired HIV-1 infection. The focus of this report is HIV-1 reservoirs and correlates in the peripheral blood of children who achieved sustained virologic suppression (SVS) for ≥5 years. Methods: HIV-1 reservoirs were determined by measuring HIV-1 DNA in peripheral blood mononuclear cells and inducible cell-free HIV-1 RNA in CD4+ T-cells by a prostratin analogue stimulation assay. HIV serology was quantified by signal-to-cutoff ratio (S/CO). Results: Of 228 enrolled participants, 69 achieved SVS for ≥5 years. HIV-1 DNA, inducible cell-free HIV-1 RNA, and S/COs correlated directly with the age of effective combination antiretroviral therapy (cART) initiation ( P < .001, P = .036, and P < .001, respectively) and age when SVS was achieved ( P = .002, P = .038, and P < .001, respectively) and inversely with the proportion of life spent on effective cART ( P < .001, P = .01, and P < .001, respectively) and proportion of life spent with SVS ( P < .001, P = .079, and P < .001, respectively). Inducible cell-free HIV-1 RNA correlated with HIV-1 DNA, most particularly in children with SVS, without virologic blips, that was achieved with the first cART regimen initiated prior to 6 months of age (rho = 0.74; P = .037) or later (rho = 0.87; P < .001). S/COs correlated with HIV-1 DNA ( P = .003), but less so with inducible cell-free HIV-1 RNA ( P = .09). Conclusions: The prostratin analogue stimulation assay, with its lower blood volume requirement, could be a valuable method for evaluating inducible HIV-1 reservoirs in children. Standard commercial HIV serology may be a practical initial indirect measure of reservoir size in the peripheral blood of children with perinatally acquired HIV-1 infection. Abstract : Human immunodeficiency virus–1 (HIV-1) reservoir sizes in peripheral blood—measured by HIV-1 DNA, inducible cell-free RNA, and quantitative serology—correlate with earlier initiation of and proportions of life spent on effective treatment and with virologic suppression.